The impact of the output gap on the unemployment rate: evidence from Mexico, 1987q1-2018q4 (2019)
Using quarterly data for Mexico from 1987Q1 to 2018Q4, we measure the impact of output gap on the unemployment rate based on a State-Space model with time-varying coefficients. From an econometric modeling point of view, this model allows asymmetrical interactions between the output gap and unemployment rate. Our principal conclusions are: 1) The long-term equilibrium unemployment rate is equal to 3.06; 2) the unemployment rate does not exhibit hysteresis; 3) when GDP is lower than potential output, the impact of its growth on the unemployment rate is -0.43 percent points; and 4) when GDP is higher than potential output, the impact of its growth on the unemployment rate is close to zero. It implies that the reaction of the unemployment rate to output gap is different when the output gap is increasing from that when the output gap is decreasing; i.e., the output gap does not have the same effect on the unemployment rate over time.